Benefits Achieved by Innovative Information Technologies and Systems In the Area of Company Process Management - Vladimír BOLEK; Michal ZELINA (Communications of International Proceedings, 2021)
Innovative pervasive technologies, information and communication technologies and information systems can help companies succeed in competition, simplify their work and make effective use of the opportunities offered, as well as identify potential threats. Their integration in business processes brings for the company/organisation several effects/ benefits in individual business areas: financial, customer, process effects. In the last decade, measuring the effectiveness and effects of information and communication technologies has become a very important issue for companies. The scientific article talks about the integration of innovative information and communication technologies and systems into business processes. It presents the results of research aimed at achieving process effects, benefits from the integration and use of these innovative technologies in enterprises.
Keywords: Information and Communication Technologies; Innovative Pervasive Technologies; Information Systems; Benefits; Process Management.